Growth performance, carcass and meat quality of lambs supplemented with increasing levels of a tanniferous bush (Cistus ladanifer L.) and vegetable oils. (February 2015) - Francisco, A.; Dentinho, M.T.; Alves, S.P.; Portugal, P.V.; Fernandes, F.; Sengo, S.; Jerónimo, E.; Oliveira, M.A.; Costa, P.; Sequeira, A.; Bessa, R.J.B.; Santos-Silva, J.
Abstract: The effects of dietary inclusion of Cistus ladanifer L. (CL) and a vegetable oil blend were evaluated on growth performance, carcass and meat quality of fifty four lambs that were assigned to 9 diets, corresponding to 3 levels of CL (50, 100 and 200 g/kg DM) and 3 levels of oil inclusion (0, 40 and 80 g/kg DM). Treatments had no effects on growth rate. Oil depressed dry matter intake (P = 0.017), carcass muscle (P = 0.041) and increased (P = 0.016) kidney knob channel fat. Chemical and physical meat quality traits were not affected by treatments. Off-flavour perception was higher for 8% of oil (P < 0.001). The level of 100 g/kg DM of CL inclusion improved meat stability after 7 days of storage. Supplementation with linseed and soybean oils (2:1) was a good approach to improve meat nutritional value from feedlot lambs, increasing total n-3 PUFA. Highlights: Cistus ladanifer can be used as an alternative forage source in lamb 's diet. Cistus ladanifer improves the colour and lipid oxidative stability of lamb's meat. Supplementation with linseed and soybean oils (2:1) increase n− 3 PUFA in lambs' meat. Both Cistus ladanifer and oil blend increased the trans fatty acids in lambs' meat.